The 21st century epidemic: Inequality in health - Irene Molero Marín (Colegio de Enfermería de Caceres, 2018)
The economic crisis has had a great impact on Spanish society, resulting in an increase in social inequality, including in the population's health.Social and economic inequalities have relevant repercussions on health. In addition, the search for a balance between health and the social situation in Spain is fundamental to improving the quality of life within society.Objective: To examine the problem of social inequalities in health in Spain since the start of the crisis to the present.Methodology: A bibliographic review is carried out using different databases and other resources. A search strategy was defined in which 41 articles were selected following the PICOT model, taking into account different inclusion and exclusion criteria.Conclusion: Although the improved economic situation in Spain is evident, there is still a long way to go before the country reaches the healthcare situation enjoyed before the crisis, which had a negative impact on Spain's National Health System and on the Spanish population, especially as regards inequality.